Revizuirea hotărârilor judecătoreşti civile pentru cazul descoperirii unor înscrisuri pobatoare noi (lit. c) art. 449 C. proc. civ. RM) - Belei, Elena (My University, 2007)
The revising of a civil judicial decision is one of the efficient remedies of civil procedural guarantees that the act of justice is well motivated and legal. The reasons for exerting the civil revision are one of the basic conditions for successful promoting of the revising request. That is why it is important to interpret and apply properly, in accordance with the tasks, main principles and the essence of civil revising the reasons of this way of appealing a civil judicial decision (art. 449 C. civ. proc. RM). One of the reasons of exerting the civil revision stipulates the case when a provable document is discovered, after the civil judicial decision is in force (lit. c) art. 449 C. civ. proc. RM). The present study has the goal to relieve the conditions of exerting the civil revision in the case when a provable document is discovered and to point out to the concepts related to it.